PROSPECT OF ZEOLITE AS ABSORBENT MATERIALS FOR REMEDIATION OF ABANDONED MINE LAND - Suwardi Suwardi; Budi Mulyanto (Institut Teknologi Bandung, 2006)
Nowdays, mining and energy are still as important sectors for contributing state economics. However, mining activitis usually make environmental problems because most of mining use open pit mining technique that causing the change for the landscape comprising topography, cover vegetation, hydrology pattern, and distruction of soils. In the consequence, the ecosystem of mining area and its surrounding will disturb. The disturbances will more clear if the overburden containing unstable minerals in oxidize condition (such as pyrite and chalcopyrite) release acid mine drained that disturbing biota growth. Zeolite is aluminosilicate mineral group having unique structure, high cation exchange capacity, porous, and adsorp of ammonium ion and water. With those properties, zeolite can be used as (a) absorp of undesirable elements or compounds such as heavy metals, (b) carrier of nutrients such as ammonium ions, and (c) increasing buffer capasity of soils. This paper will dicuss the prospect of zeolite as material for remediation of abandoned mine land.